2015
DOI: 10.1371/journal.pone.0139144
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis Pneumonia in Patients with Autoimmune Diseases: A Retrospective Study Focused on Clinical Characteristics and Prognostic Factors Related to Death

Abstract: BackgroundWith the increasing use of immunosuppressive agents, the number of opportunistic infections has risen in patients with autoimmune diseases. Pneumocystis pneumonia (PCP) is one of these opportunistic infections that have a high mortality rate. However, only a few studies have described PCP in these patients, and these studies are limited in scope. We conducted this retrospective study to describe the clinical characteristics and factors associated with outcomes of PCP in patients with autoimmune disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 24 publications
2
44
0
3
Order By: Relevance
“…A CD4+ cell count of less than 200 cells/mm 3 after 1 month of immunosuppressive therapy is another alternative indication to provide PCP prophylaxis in this group. The CD4+ cell count should be monitored in patients who receive more than 15 mg prednisolone or equivalent per day, a corticosteroid for more than 3 months, or with a total lymphocyte count of less than 600 cell/mm 3 (2,14). The timing of the start of prophylaxis therapy as well as the duration and the timing of the discontinuation of therapy may need further investigation in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CD4+ cell count of less than 200 cells/mm 3 after 1 month of immunosuppressive therapy is another alternative indication to provide PCP prophylaxis in this group. The CD4+ cell count should be monitored in patients who receive more than 15 mg prednisolone or equivalent per day, a corticosteroid for more than 3 months, or with a total lymphocyte count of less than 600 cell/mm 3 (2,14). The timing of the start of prophylaxis therapy as well as the duration and the timing of the discontinuation of therapy may need further investigation in this group.…”
Section: Discussionmentioning
confidence: 99%
“…including those with connective tissue disease, is increasing (1,2). Chen et al (3) found 69 (26.1%) patients with autoimmune diseases who were diagnosed with PCP over a 10-year period. PCP infection in systemic lupus erythematosus (SLE) patients is uncommon, but it may be fatal (4).…”
Section: öZetmentioning
confidence: 99%
“…В некоторых работах обращается внимание на сниже-ние абсолютного числа лимфоцитов у больных системны-ми РЗ, у которых в дальнейшем развилась ППн [3,9,[10][11][12][13]. Однако контрольная «точка отсечения» уровня лимфоцитов, при которой следует начинать профилакти-ку, до сих пор дебатируется.…”
Section: факторы риска инфекцииunclassified
“…[9]. Среди прочих факто-ров риска летального исхода при ППн называют пожилой возраст, мужской пол, сниженное содержание кислорода во вдыхаемом воздухе, необходимость меха нической венти-ляции легких, снижение содержания сывороточного альбу-мина [3,12]. В целом каких-либо определенных факторов риска летальности, ассоциированной с ППн, у больных системными РЗ не установлено.…”
Section: летальностьunclassified
See 1 more Smart Citation